Perspectives on access and usage of assistive technology by people with intellectual disabilities in the Western Cape province of South Africa: Where to from here? - Boot, Fleur H; Kahonde, Callista; Dinsmore, John; MacLachlan, Malcolm (African journal of disability, 2021)
BACKGROUND: Whilst assistive technology (AT) can play an important role to improve quality of life, health inequity regarding access to appropriate AT for people with intellectual disabilities (ID) is still very much present especially in low resource countries. OBJECTIVES: This study focused on exploring factors that influence access to and continued use of AT by people with ID in the Western Cape province of South Africa and to suggest potential implications of these findings and actions required to promote access to AT. METHOD: A qualitative approach was used to explore the experiences of people with ID and providers of AT. Face-to-face interviews with 20 adults with mild to profound ID, and 17 providers of AT were conducted and the data were analysed thematically. RESULTS: People with ID within the study setting faced many challenges when trying to access AT and for those who managed to acquire AT, its continued usage was influenced by both personal characteristics of the user and environmental factors. Important factors that influence AT access and use for people with ID found in this study were (1) attitudes from the community, (2) knowledge and awareness to identify AT need and (3) AT training and instructions to support the user and care network. CONCLUSION: With the perspectives of both the providers and users of AT, this study identified priority factors, which could be addressed to improve AT access and use for people with ID in the Western Cape province.
Keywords: health inequity; intellectual disability; South Africa; assistive technology; access